The stronghold on Kirkut Hill in Lublin. The state of recognition of the remains of the former stronghold and its role in the medieval Lublin agglomeration - Niedźwiadek, Rafał; Rozwałka, Andrzej (Analecta Archaeologica Ressoviensia, 2020)
The aim of the article is to present the state of the research conducted on the remains of a medieval stronghold on Grodzisko Hill, also known as Kirkut Hill (due to the Jewish cemetery from the late Middle Ages and early modern period located on its top), as well as to show the latest approach to dating the remains of the stronghold and its role in the medieval Lublin agglomeration. Archaeological research carried out on the hill and at its foot in the 1960s and 1970s was of limited range due to the existence of the Jewish cemetery. However, it can be considered that they provided an amount of data that enables the reconstruction of stratigraphy of the stronghold and recognition of the structure of its rampart running along the edge of the hill. After many discussions, both among historians and Lublin archaeologists, a certain consensus regarding the chronology and the function of the former stronghold on Grodzisko Hill has now been reached. It seems that it was in the 13th century that the stronghold was built and, then, before the century ended, it was destroyed. It coexisted with an older structure – probably built in the 12th century – namely the castellan stronghold on Zamkowe Hill. Recent research indicates that during the second half of 13th century, or at the turn of the 13th and 14th centuries, a new line of ramparts was built on Staromiejskie Hill. This is how three parts of the Lublin agglomeration were distinguished. Perhaps, in this structure, the stronghold on Kirkut Hill could have functioned as a guard post for a part of the long-distance route located in the area of today’s Kalinowszczyzna Street. The 13th century, and especially its second half, was the time of numerous Yotvingian, Lithuanian, Mongolian, Ruthenian and Tatar invasions.